Clinicopathological Characteristics and Prognosis in Endometrial Cancer With Bone Metastasis: A SEER-Based Study of 584 Women - Hu, Hejia; Wang, Zhan; Zhang, Miaofeng; Niu, Feng; Yu, Qunfei; Ren, Ying; Ye, Zhaoming (Frontiers in Oncology, 2021)
Purpose Bone metastasis from endometrial cancer (EC) is rare and poorly described. The purpose of the present study was to investigate the correlation between the clinically accessible factors and survival time among EC patients with bone metastasis. Patients and Methods We retrospectively identified and reviewed EC patients with bone metastasis from 2010 to 2016, based on the Surveillance, Epidemiology and End Results (SEER) database. Univariable and multivariable Cox regressions were applied to evaluate the effects of clinical variables on survival. Kaplan–Meier plots were used to visually demonstrate the correlation between independent risk factors and survival. Results Clinical data of 584 EC patients with bone metastasis from the SEER database were analyzed. EC patients with bone metastasis experienced extremely poor survival, with 1-year overall survival (OS) and cancer-specific survival (CSS) rates 33.8 and 35.8%, respectively. Variables associated with OS and CSS in the univariable analysis included race, tumor grade, tumor subtype, tumor size, lung, liver and brain metastases, surgery, radiotherapy, and chemotherapy. In the multivariable analysis, tumor grade, tumor subtype, liver and brain metastases, local surgery, and systemic chemotherapy remained independent risk factors for OS and CSS. However, local radiotherapy was an independent predictor of OS, not CSS. Conclusions We identified several factors affect the survival of EC patients with bone metastasis, which is useful for clinicians to assess patients’ outcomes. Our study supports surgery and radiotherapy of primary EC, and systemic chemotherapy for prolonging survival among EC patients with bone metastasis, which lays a solid foundation for defining optimal treatment strategy in this specific cohort.